Pulse Amplitude and Delay Modulation: Design and performance analysis - Slaiman, I. (Elsevier B.V., 2015)
Power efficient modulation techniques have previously been proposed to provide the uplink in visible light communication systems. However, such techniques have poor bandwidth utilization as multiple bits are mapped to single narrow pulse. When the bandwidth is limited, it has been found that degradation in optical power becomes very high and data rate poor. In this paper we introduce a new modulation technique called Pulse Amplitude and Delay Modulation (PADM). We compare its performance with Dual Header Pulse Interval Modulation (DH-PIM) that has the best reported bandwidth efficiency. Experiment results show that the data rate could be enhanced from 3.2 kps to 4.3 kbs using a red link (640 nm) under same error rate. This suggests PADM has better bandwidth efficiency than DH-PIM. Â© 2015 Elsevier B.V.